2020
DOI: 10.1016/j.jad.2020.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Financial threat, hardship and distress predict depression, anxiety and stress among the unemployed youths: A Bangladeshi multi-city study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 67 publications
4
47
2
1
Order By: Relevance
“…Results from our study also indicate that nancial di culties caused by the COVID 19 pandemic played a crucial role when predicting all three mental health problems of HCW we have measured. The mental health impact of nancial issues among HCW during this pandemic time is yet to be evaluated elaborately, however, the previous study showed a highly signi cant association between nancial hardship and mental health among Bangladeshi professionals [22]. Further evaluation is warranted to nd in-depth predicting nature of the nancial issues raised due to the COVID-19 pandemic to the mental health of sufferers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Results from our study also indicate that nancial di culties caused by the COVID 19 pandemic played a crucial role when predicting all three mental health problems of HCW we have measured. The mental health impact of nancial issues among HCW during this pandemic time is yet to be evaluated elaborately, however, the previous study showed a highly signi cant association between nancial hardship and mental health among Bangladeshi professionals [22]. Further evaluation is warranted to nd in-depth predicting nature of the nancial issues raised due to the COVID-19 pandemic to the mental health of sufferers.…”
Section: Discussionmentioning
confidence: 96%
“…The total score ranges from 0 to 27. The total score suggests different levels of depressive symptoms: minimal/no depression (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19)(20)(21), and very severe (22)(23)(24)(25)(26)(27). However, in this study, cut-off point ≥ 10 was used to classify participants as having depressive symptoms [14,15].…”
Section: Depression Symptomsmentioning
confidence: 99%
“…There are growing pieces of evidence that indicate role of financial crisis and its economic fallout on mental instability ( Oyesanya et al, 2015 ; Rafi et al, 2019 ). People with sudden poverty and economic distress may face life-threatening situation ( Mamun et al, 2020e ). This is true even in high-income countries of Europe and North America; Oyesanya et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, without proper safety measures, the HCPs are also in dilemma whether to continue the job or not owing to personal and family protection. In some cases, their such decision made them fall into the state of partial unemployment which may aggravate mental sufferings during the crisis period ( Dhaka Tribune, 2020c ; Mamun et al., 2020b ; Rafi et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%